An Interactive dashboard to automate data cleaning, processing, analysis to produce crop and location specific farm advisories. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We have developed scripts for data cleaning and processing. We are now developing scripts for range of predictive and optimization modelling. In parallel, we are also developing a schema to automate all of these processes through data cleaning to production of knowledge product in the form of dashboard.